The giver - Lowry, Lois. (Laurel Leaf Books, 2002)
Lowry's unforgettable tale introduces 12-year-old Jonas, who is singled out by the Community to be trained by The Giver. The Giver alone holds the memories of true pain and pleasure. Now it's time for Jonas to receiver the truth.